Penegakan Hukum Terkait Kontrak dan Jam Kerja Fleksibel: Perspektif Pekerja dan Regulasi Ketenagakerjaan - Yuli Agung Nugroho; Haza Irsyadul Furqan Bachri (MISTER: Journal of Multidisciplinary Inquiry in Science, Technology and Educational Research, 2024)
Contracts and flexible working hours have become a common option in modern employment practices. Contracts and flexible working hours provide adaptability for companies and workers in facing changing market dynamics. However, behind the practicality offered, there are a number of legal issues that require serious attention. This article aims to investigate the enforcement of laws related to contracts and flexible working hours, with a focus on workers' perspectives and employment regulations. The research method used in this article is literature analysis. This approach involves the collection and critical analysis of relevant academic literature, legal documents and case studies to explain the complexities of flexible employment contracts from a legal perspective. Through this approach, this article identifies the challenges faced by workers in flexible work contracts, including the protection of their rights, job stability and social security. In addition, this article also explores the response and effectiveness of current employment regulations in addressing issues related to contracts and flexible working hours.